2021
DOI: 10.1002/ijgo.14037
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia during the oral glucose tolerance test in pregnancy—maternal characteristics and neonatal outcomes

Abstract: Gestational diabetes mellitus (GDM) is manifested by carbohydrate intolerance that develops during pregnancy and is associated with adverse maternal and neonatal outcomes. 1 In 2014, the US Preventive Services Task Force made a recommendation to screen all pregnant women for GDM at or beyond 24 weeks of gestation. 2 Screening is generally performed using the two steps approach: a 50-g glucose challenge test (GCT) at 24-28 weeks, followed by a diagnostic 100-g oral glucose tolerance test (OGTT) for those who sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Meta-analysis of RCTs on the effects of probiotics on glycemia in pregnancy by Pan et al (2021) indicated that probiotic supplements improved FPG level (14 RCTs) and insulin resistance (HOMA-IR, 13 RCTs), specifically in GDM and healthy pregnant women, which is in trend with our results regarding nutritional supplements and improved levels of FPG and HOMA-IR [ 52 ]. Maternal age is a known confounder of glucose status with dysglycemic individuals typically older [ 53 ]. Our results suggest that nutritional supplements are less effective in reducing insulin resistance in the higher maternal age subgroup, as this group might have more severe dysglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis of RCTs on the effects of probiotics on glycemia in pregnancy by Pan et al (2021) indicated that probiotic supplements improved FPG level (14 RCTs) and insulin resistance (HOMA-IR, 13 RCTs), specifically in GDM and healthy pregnant women, which is in trend with our results regarding nutritional supplements and improved levels of FPG and HOMA-IR [ 52 ]. Maternal age is a known confounder of glucose status with dysglycemic individuals typically older [ 53 ]. Our results suggest that nutritional supplements are less effective in reducing insulin resistance in the higher maternal age subgroup, as this group might have more severe dysglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis suggested that common moderators of GDM risk do not modify the effectiveness of dietary interventions on dysglycemia, except for lower maternal age, ADA diagnostic criteria, and a non-western country. Pregnant women with lower maternal age are less likely to suffer from severe dysglycemia; thus, interventions might be more effective and insulin resistance might be easier to improve in this subgroup [ 53 ]. All non-western country studies used ADA guidelines as diagnostic criteria, suggesting a disagreement of diagnostic criteria as a previous study found IADPSG (i.e., ADA) criteria more favorable than NICE for identification of adverse pregnancy outcomes among Asian and Hispanic women, while they are comparable to NICE among White women [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies have focused on the potential relationship between low glycemia during the oral glucose tolerance test (OGTT) and the impact on maternal and neonatal outcomes in normal glucose tolerant (NGT) women. Studies focused mostly on the effects of reactive hypoglycemia during an OGTT (7,8,(12)(13)(14)(15)(16) and data are limited on the potential effects of lower glycemic values in general. In addition, these studies reported conflicting results concerning the impact on maternal and neonatal outcomes, especially on neonatal birth weight (7,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused mostly on the effects of reactive hypoglycemia during an OGTT (7,8,(12)(13)(14)(15)(16) and data are limited on the potential effects of lower glycemic values in general. In addition, these studies reported conflicting results concerning the impact on maternal and neonatal outcomes, especially on neonatal birth weight (7,(12)(13)(14). Moreover, most studies investigated the effects of hypoglycemia in women with GDM or obesity (12,14,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation